Once Upon a Time in Texas A Liberal in the Lone Star State - Richards, David (University of Texas Press, 2021)
Once upon a time in Texas.there were liberal activists of various stripes who sought to make the state more tolerant and more tolerable. David Richards was one of them. In this fast-paced, often humorous memoir, he remembers the players, the strategy sessions, the legal and political battles, and the wins and losses that brought significant gains in civil rights, voter rights, labor law, and civil liberties to the people of Texas from the 1950s to the 1990s. In his work as a lawyer, Richards was involved in cases covering voters' rights, school finance reform, and a myriad of civil liberties and free speech cases. In telling these stories, he vividly evokes the "glory days" of Austin liberalism, when a who's who of Texas activists plotted strategy at watering holes such as Scholz Garden and the Armadillo World Headquarters. Likewise, he offers vivid portraits of liberal politicians from Ralph Yarborough to Ann Richards (his former wife), progressive journalists such as Molly Ivins and the Texas Observer staff, and the hippies, hellraisers, and musicians who all challenged Texas's conservative status quo